Cylindrical dye-sensitized solar cells with high efficiency and stability over time and incident angle. Issue 17 (3rd February 2016) - Tang, Qunwei; Zhang, Lei; He, Benlin; Yu, Liangmin; Yang, Peizhi
Abstract : The presented cylindrical dye-sensitized solar cells are remarkably stable over time and incident angle. Abstract : We present here the realization of cylindrical dye-sensitized solar cells composed of Ti wire supported TiO2 nanotube anodes and transparent metal selenide counter electrodes. The optimized device yields a high efficiency of 6.63%, good stability over time, and identical efficiency output at arbitrary incident angles.